2023
DOI: 10.1007/s40519-023-01552-5
|View full text |Cite
|
Sign up to set email alerts
|

The factors associated with orthorexia nervosa in type 2 diabetes and their effect on diabetes self-management scores

Abstract: Purpose This study aimed to determine the factors affecting the ORTO-R scores in individuals with T2DM and to investigate their effect on diabetes self-management. Methods The study included 373 individuals with type 2 diabetes between the ages of 18–65 who applied to Akdeniz University Hospital Endocrinology and Metabolic Diseases Polyclinic between January and May 2022. A questionnaire including sociodemographic data, information about diabetes, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Individuals who were graduates showed the highest prevalence of EDs as compared to participants who had primary or secondary education. This positive correlation with education contradicts a study finding that investigated the unclassifiable EDs and found the association the other way around [29], and further investigation may be warranted to explore the underlying factors contributing to this association. Similarly, a correlation between exercise and EDs was also seen in our study.…”
Section: Discussioncontrasting
confidence: 87%
“…Individuals who were graduates showed the highest prevalence of EDs as compared to participants who had primary or secondary education. This positive correlation with education contradicts a study finding that investigated the unclassifiable EDs and found the association the other way around [29], and further investigation may be warranted to explore the underlying factors contributing to this association. Similarly, a correlation between exercise and EDs was also seen in our study.…”
Section: Discussioncontrasting
confidence: 87%
“…However, the focus on maintaining a healthy diet in diabetes management can sometimes lead to orthorexic tendencies. The strict rules and restrictions associated with diabetes self-management may trigger obsessive thoughts and behaviors around food quality and purity [ 91 ]. These individuals may become overly fixated on only consuming “healthy” foods and avoiding any perceived “unhealthy” or “impure” choices, which can contribute to the development or exacerbation of ON.…”
Section: Diabetes and Disordered Eating Behaviors/eating Disordersmentioning
confidence: 99%